Analisis Cost-Volume-Profit Sebagai Alat Perencanaan Laba Jangka Pendek Pada Cousin Coffee & Eatery - Lengkong, Angelina Elsy; Pontoh, Winston; Kalalo, Meily Y. B. (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Cost Volume Profit analysis is a management tool in conducting profit planning for the company. Cost Volume Profit analysis can make it easier for companies to determine revenue targets and the amount of costs incurred in an effort to achieve profit targets. This analysis has several components of analysis including contribution margin, break even point, margin of safety and operating leverage, shut down point and profit target analysis. The purpose of this study is to determine the profit planning at PT. Air Manado by using Cost-Volume-Profit analysis. The research method used is descriptive method. Based on the results of this study it is known that the cost profit volume analysis for the profit planning in 2022 showed that Cousin Coffee & Eatery was able to cover its fixed costs and earn a profit with a contribution margin of Rp333,976,953 or 77%. Cousin Coffee & Eatery is at breakeven point of Rp31,969,264 if it is able to reach a sales volume of Rp429,773,456. While the margin of safety, sales can decline so as not to cause losses is Rp397,804,192 or 92.56%. Then for operating leverage shows the number 1.08. Furthermore, the shut down point for profit planning of 2022 Cousin Coffee & Eatery in 2022 is at its closing point of Rp31,969,264 which means Cousin Coffee & Eatery must generate sales above that amount in order to finance its cash costs. To get a 50% increase in profit or profit of Rp309,360,620, Cousin Coffee & Eatery must increase sales by Rp429,773,456. Variable costs will also increase following the increase in production costs, while fixed costs are assumed to be constant or unchanged.